1997
DOI: 10.1016/s0014-5793(97)00176-2
|View full text |Cite
|
Sign up to set email alerts
|

Glutamine‐330 is not essential for activity in isopenicillin N synthase from Aspergillus nidulans

Abstract: © 1997 Federation of European Biochemical Societies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
1

Year Published

1998
1998
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 15 publications
2
33
1
Order By: Relevance
“…In contrast, the DAOCS structure reveals only three protein-derived iron ligands and the EXAFS data do not provide evidence for a fourth protein ligand. Thus, the DAOCS studies support mutagenesis studies with IPNS, concluding that iron ligation by a C-terminal residue is not required for catalysis (Sami et al, 1997;Borovok et al, 1996). The structures suggest that the DAOCS C terminus may assist in ordering binding of substrates to the active site.…”
Section: Role Of the C Terminus And Substrate Bindingsupporting
confidence: 53%
See 1 more Smart Citation
“…In contrast, the DAOCS structure reveals only three protein-derived iron ligands and the EXAFS data do not provide evidence for a fourth protein ligand. Thus, the DAOCS studies support mutagenesis studies with IPNS, concluding that iron ligation by a C-terminal residue is not required for catalysis (Sami et al, 1997;Borovok et al, 1996). The structures suggest that the DAOCS C terminus may assist in ordering binding of substrates to the active site.…”
Section: Role Of the C Terminus And Substrate Bindingsupporting
confidence: 53%
“…As noted previously (Sami et al, 1997;Zhang et al, 1997) the errors in apparent K m and k cat values determined from preliminary steady-state kinetic analysis for Fe(II)-dependent oxidizing enzymes may well be signi®cant and caution should be exercised in drawing mechanistic conclusions from relatively small (i.e. less than an order of magnitude) differences.…”
Section: Resultsmentioning
confidence: 95%
“…There are precedents for a role of the C-terminus of 2OG oxygenases in substrate binding and selectivity (27)(28)(29)(30). However, removal of the C-terminal residues 403-426 from PHD2 181-426 affects neither its ability to decarboxylate 2OG, nor its ability to hydroxylate CODD or NODD substrates when peptide substrates were assayed separately.…”
Section: Discussionmentioning
confidence: 99%
“…Binding experiments were performed over a range of concentrations and kinetic data were calculated using the BIAevaluation software (GE Healthcare). -Studies on some 2OG oxygenases from the subfamily to which the PHDs belong have revealed a role for the C-terminus of the enzyme in substrate binding and selectivity (23,(27)(28)(29)(30). Alignment of the three human PHD isoform sequences combined with information from the crystal structure of PHD2 181-426 (24) (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Deletion of six amino acids from the C terminus of Aspergillus nidulans IPNS (Sami et al, 1997) or Streptomyces clavuligerus DAOCS (Valegard et al, 1998) significantly diminished the activity and it was suggested that the enzymes, which accommodate the active site in a b-sheet barrel, use the C terminus as a protective lid to maintain a hydrophobic environment and to enable proper cofactor binding (Lloyd et al, 1999). In the case of chimeric GA 20-oxidases, a pronounced influence of the C terminus on product selectivity was noticed (Lange et al, 1997).…”
Section: Significance Of the C Terminusmentioning
confidence: 99%